2003
DOI: 10.1046/j.1469-8137.2003.00746.x
|View full text |Cite
|
Sign up to set email alerts
|

Differential heavy metal tolerance of Arabidopsis halleri and Arabidopsis thaliana: a leaf slice test

Abstract: Summary• Here, a short-term leaf tissue tolerance test was designed to determine the distinct Zn-, Cd-and Ni-tolerance levels for leaves of the Zn-hyperaccumulating plant Arabidopsis halleri compared with Arabidopsis thaliana .• Leaf slices were incubated in different metal concentrations for 2 h. Quantum yield of photosystem II was used as a parameter dependent on heavy metal concentrations in the incubation medium.• The half effective concentration values (EC50) showed that A. halleri was extremely tolerant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
34
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(35 citation statements)
references
References 20 publications
1
34
0
Order By: Relevance
“…The results for the M populations presented here describe the toxic effect of HM on the PSII activity parameters, such as wP 0 , that are measured in situ (Table IV). There is a dearth of articles presenting the results of PSII activity in situ, but some studies that have been performed in controlled conditions showed that this parameter (also known as F v /F m ) decreases under the toxic effects of Cd (Cho et al, 2003;Zhou and Qiu, 2005;Küpper et al, 2007;Maksymiec et al, 2007), Pb (Kalaji and Loboda, 2007), and Zn (Cho et al, 2003;Przedpelska-Wasowicz and Wasowicz, 2013). The hyperaccumulators (e.g.…”
Section: The Impact Of Environmental Factors On the Photosynthetic Apmentioning
confidence: 99%
See 2 more Smart Citations
“…The results for the M populations presented here describe the toxic effect of HM on the PSII activity parameters, such as wP 0 , that are measured in situ (Table IV). There is a dearth of articles presenting the results of PSII activity in situ, but some studies that have been performed in controlled conditions showed that this parameter (also known as F v /F m ) decreases under the toxic effects of Cd (Cho et al, 2003;Zhou and Qiu, 2005;Küpper et al, 2007;Maksymiec et al, 2007), Pb (Kalaji and Loboda, 2007), and Zn (Cho et al, 2003;Przedpelska-Wasowicz and Wasowicz, 2013). The hyperaccumulators (e.g.…”
Section: The Impact Of Environmental Factors On the Photosynthetic Apmentioning
confidence: 99%
“…Parameters are as follows: F 0 , minimal fluorescence, when all of the PSII RCs are open (at time 0); F m , maximal fluorescence, when all of the PSII RCs are closed; F v , maximum variable fluorescence; wP 0 , maximum quantum yield of the primary PSII photochemistry; CE 0 , probability (at time 0) that a trapped exciton moves an electron into the electron transport chain beyond Q A -; wE 0 , quantum yield for electron transport from Q A 2 to plastoquinone; dR 0 , probability that an electron from the intersystem electron carriers will move to reduce the end acceptors at the PSI acceptor side; wR 0 , quantum yield for the reduction of the end electron acceptors at the PSI acceptor side; wD 0 , quantum yield (at time 0) of energy dissipation; T Fm , time (in ms) to reach F m ; Area, total complementary area between the fluorescence induction curve and F = F m (total plastoquinone pool). and Sedum alfredii) and tolerant plants (Arabidopsis arenosa) were characterized by a minor although relevant decrease of wP 0 under high HM doses (up to 2,000 mM Zn and 1,000 mM Cd; Cho et al, 2003;Zhou and Qiu, 2005;Küpper et al, 2007;Przedpelska-Wasowicz and Wasowicz, 2013) The nontolerant plants (e.g. A. thaliana and Hordeum vulgare) were characterized by significant decreases in PSII activity under relatively low doses of Cd (100 mM Cd had a lethal effect; Cho et al, 2003;Kalaji and Loboda, 2007;Maksymiec et al, 2007).…”
Section: The Impact Of Environmental Factors On the Photosynthetic Apmentioning
confidence: 99%
See 1 more Smart Citation
“…It is caused by a wide variety of compounds, including heavy metals, salinity, pesticides, phytotoxins or allelopathy. The sensitivity of plants to heavy metals depends on an interrelated network of physiological and molecular mechanisms such as uptake and accumulation of metals from cytoplasm to extra cellular exudates and cell wall constituents; efflux of heavy metals from cytoplasm to extra nuclear compartments including vacuoles; complexation of heavy metal ions inside the cell by various substances, for example, organic acids, phytochelatins, amino acids and metallothioneins; accumulation of osmolytes and induction of antioxidative enzymes; activation or modification of plant metabolism to allow adequate functioning of metabolic pathways and rapid repair of damaged cell structures [1]. Cadmium (Cd), being highly toxic metal pollutants of soils, which inhibits the root and shoot growth (yield), affects nutrient uptake.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that metal tolerance and accumulation traits vary as a function of the plant origin . In recent years, Arabidopsis halleri has been intensively studied for the genetics and physiology of metal tolerance and hyperaccumulation (KUPPER et al, 2000;ZHAO et al, 2000;ZHAO et al, 2006;CHO et al, 2003;BECHER et al, 2004;WEBER et al, 2004). Moreover, this species develops populations on contaminated and uncontaminated soil .…”
Section: Introductionmentioning
confidence: 99%